2021
DOI: 10.3389/fmolb.2021.632290
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Exosomes Are Strongly Involved in SARS-CoV-2 Infection

Abstract: Knowledge of the host response to the novel coronavirus SARS-CoV-2 remains limited, hindering the understanding of COVID-19 pathogenesis and the development of therapeutic strategies. During the course of a viral infection, host cells release exosomes and other extracellular vesicles carrying viral and host components that can modulate the immune response. The present study used a shotgun proteomic approach to map the host circulating exosomes’ response to SARS-CoV-2 infection. We investigated how SARS-CoV-2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
213
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(230 citation statements)
references
References 78 publications
16
213
0
1
Order By: Relevance
“…Previous study focus on patients during the disease revealed DEPs between COVID-19 patients and healthy control. In that study, Elettra Barberis et al found that DEPs were mainly belonged to three functional enrichments, inflammatory, immune response, and coagulation, while we found the DEPs between recovered COVID-19 patients and healthy subjects mainly focus on lipid metabolic process, response to cellular, and response to stress oxygen-containing compound, suggesting that different biological characteristics also occurred between recovered COVID-19 patients and patients during the disease 15 . Through analyzing DEPs, we found that some acute phase associated proteins decreased in severe recovered patients such as apolipoprotein APOC4 and CPB1 protein, while the regulator of complement system CPN1 protein was elevated.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Previous study focus on patients during the disease revealed DEPs between COVID-19 patients and healthy control. In that study, Elettra Barberis et al found that DEPs were mainly belonged to three functional enrichments, inflammatory, immune response, and coagulation, while we found the DEPs between recovered COVID-19 patients and healthy subjects mainly focus on lipid metabolic process, response to cellular, and response to stress oxygen-containing compound, suggesting that different biological characteristics also occurred between recovered COVID-19 patients and patients during the disease 15 . Through analyzing DEPs, we found that some acute phase associated proteins decreased in severe recovered patients such as apolipoprotein APOC4 and CPB1 protein, while the regulator of complement system CPN1 protein was elevated.…”
Section: Discussionmentioning
confidence: 50%
“…Through analyzing DEPs, we found that some acute phase associated proteins decreased in severe recovered patients such as apolipoprotein APOC4 and CPB1 protein, while the regulator of complement system CPN1 protein was elevated. In previous study, there is some acute phase associated proteins such as Alpha 1-antichymotrypsin and CRP protein increased in EVs from severe patients during the disease 15 . In other word, APOC4 and CPB1 proteins were damaged, which may be associated with the degree of infection.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Indeed, proteomic analysis of the EV in plasma of patients with different degrees of COVID-19 severity showed distinct protein signatures that correlate with clinical manifestations of the disease [ 184 ]. In a separate study, Barberis et al found that the proteome of the circulating EVs contained a large number of immune, pro-inflammatory and pro-coagulant proteins, and identified SARS-Cov-2 RNA in the exosomal cargo [ 185 ]. In a recent study, human lung endothelial cells exposed to the plasma of patients with severe disease and the plasma of patients with mild disease showed a significant difference in caspase3/7 and decreased cell survival in the former [ 186 ].…”
Section: The Biological and Clinical Relevance Of Endothelial Evs In Covid-19mentioning
confidence: 99%
“…Albeit pioneering studies have been focused on anti-cancer therapies, the attention has now shifted to viral disease. Of note, EVs are also used as biomarkers of several human diseases, including viral infections [121,122].…”
Section: Evs As Delivery Systems In Vaccinesmentioning
confidence: 99%